Exploring challenges and lessons learned in cross-cultural environmental education research. (April 2019) - Briggs, Lilly; Trautmann, Nancy; Phillips, Tina
Highlights: Cross-cultural environmental education research poses unique challenges. Survey adaptation for multicultural use requires going beyond translation. Research approaches must appropriately address language and sociocultural factors. A collaborative, iterative process with partners is necessary for developing tools and measures. Abstract: The field of environmental education (EE) has been criticized for scarcity of research findings that can be used to compare the approaches and outcomes of various interventions and contexts. This is particularly problematic for EE programs that are implemented across multi-cultural settings because very little academic attention has been devoted to cross-cultural EE research methods. Intending to address this gap, we set out to develop and pilot a pre/post survey in Costa Rica that could help us investigate the impacts of a bird-focused curriculum on Latin American children's knowledge, attitudes, behavioral intentions, and behaviors toward birds and the natural world. This article describes the challenges encountered and subsequent adaptations made throughout our ongoing, iterative survey development process, in order to appropriately address language, sociocultural context, audience, and research-to-practice tensions. We present key lessons learned, including the importance of having strong local partners, the need to create a realistic research timetable that accounts for unique challenges involved in undertaking cross-cultural EE research, and the limitations of quantitative methods in this sort of research.